If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
x+(4/3)*x = 49 // - 49
x+(4/3)*x-49 = 0
7/3*x-49 = 0 // + 49
7/3*x = 49 // : 7/3
x = 49/7/3
x = 21
x = 21
| Y=x^2-18x+13 | | 5x+5-4x=8+2x-7 | | ((x+3)/(4))-((x-4)/(2))=(3/8) | | -12-10=x | | -9t-37=8 | | 3(m+5)-6=5(m-2)-7 | | 10x+5-1=44 | | .3x-3=.1(x+30) | | 5-((3a-4)/(5))=((7-2a)/(2)) | | x^2+8x+29=0 | | x+2/3=y-1/2 | | 1/7f-11/2=9/14 | | 3x^2-1=95 | | -5+9=x | | -3r+18=3 | | 2(x-2)=3(x+6) | | 6x-6y=20 | | Y=3power(x-2) | | 3(x+2)=5(x-6) | | Y=3powerx-2 | | 0.3n=36 | | 2x^2+5x=403 | | 3s-(4)=8 | | -[3x+(5x+8)]=6-(2x+9) | | 2g-(3)=-9 | | (8/9)-(64/81)=x | | 5t-(4)=6 | | 5w-(12)=3 | | x+3x=672 | | y-4/7=-3/14 | | d^2+520d=5300 | | x=-3x-24 |